Embryonic development - Selby, Charles Baxter (My University, 1895)
Introduction: In the world of animal organisms is found one of the most comprehensive studies with which mankind interests himself, and in which the supernatural work and wisdom of God is exemplified. No study affords more opportunity for continued thought and extended investigation. Although mankind continues to add to this already vast accumulation of facts which began primarily with the advent of man, yet, seemingly, it approaches but little nearer a complete science, than it was when its principles were first enunciated by the Grecian writers. The reason for this seeming incompleteness is due to the fact that so many intricate questions and discoveries must be accounted for, and these again explained. The more facts discovered, the more must be explained; and it seems we will never reach, what we term an exhaustive and adequate knowledge of this, a branch of the most complex of the natural sciences.
Citation: Selby, Charles Baxter. Embryonic development. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Biology; Embryonic development; Theses; Manuscripts (documents)